Using Educational Media to Prevent Adolescent Smoking and Raise Health Awareness: A Meta-Analysis - Meylida Swatitis Kurnia Saputri; Puspita Sari, Sella; Syamsulhuda Budi Mustofa; Lestantyo, Daru (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2024)
Background: Adolescent smoking has become a significant public health problem with a growing prevalence in many parts of the world. Aims: This study aims to analyze the use of appropriate educational media on the dangers of smoking for adolescents. Methods: This study used a scoping review method, with sources from Google Scholar and Scopus from 2019 to 2024. The keywords used in the search included combinations of terms such as “educational media”, “smoking hazard”, “adolescents”, “smoking prevention”, and others. In addition, reference lists of relevant studies were also searched to identify additional sources that may be relevant. Results: The results show that from 2020 to 2024, there were 972 articles in Google Scholar, while in Scopus, 108 databases were found. Based on the research results, it can be concluded that educational media that are interactive, visually appealing, and utilize digital technology, such as animated videos, tend to be more effective than traditional educational media, such as advertising videos or leaflets. Conclusion: Other interactive educational media, such as mobile game applications, have also been effective in improving adolescents' understanding due to their fun and self-accessibility. Although video advertisements and leaflets are also effective, they are less effective than interactive digital educational media. This is in line with the preferences of today's adolescents, who are more interested in interactive visual content and digital technology. In designing educational media, it is essential to involve adolescents to ensure that it meets their preferences and needs.